Glucose metabolism down‐regulates the uptake of 6‐(N‐(7‐nitrobenz‐2‐oxa‐1, 3‐diazol‐4‐yl)amino)‐2‐deoxyglucose (6‐NBDG) mediated by glucose transporter 1 isoform (GLUT1): theory and simulations using the symmetric four‐state carrier model. (27th February 2013) - DiNuzzo, Mauro; Giove, Federico; Maraviglia, Bruno; Mangia, Silvia
Abstract: The non‐metabolizable fluorescent glucose analogue 6‐(N‐(7‐nitrobenz‐2‐oxa‐1, 3‐diazol‐4‐yl)amino)‐2‐deoxyglucose (6‐NBDG) is increasingly used to study cellular transport of glucose. Intracellular accumulation of exogenously applied 6‐NBDG is assumed to reflect concurrent gradient‐driven glucose uptake by glucose transporters (GLUTs). Here, theoretical considerations are provided that put this assumption into question. In particular, depending on the microscopic parameters of the carrier proteins, theory proves that changes in glucose transport can be accompanied by opposite changes in flow of 6‐NBDG. Simulations were carried out applying the symmetric four‐state carrier model on the GLUT1 isoform, which is the only isoform whose kinetic parameters are presently available. Results show that cellular 6‐NBDG uptake decreases with increasing rate of glucose utilization under core‐model conditions, supported by literature, namely where the transporter is assumed to work in regime of slow reorientation of the free‐carrier compared with the ligand–carrier complex. To observe an increase of 6‐NBDG uptake with increasing rate of glucose utilization, and thus interpret 6‐NBDG increase as surrogate of glucose uptake, the transporter must be assumed to operate in regime of slow ligand–carrier binding, a condition that is currently not supported by literature. Our findings suggest that the interpretation of data obtained with NBDG derivatives is presently ambiguous and should be cautious because the underlying transport kinetics are not adequately established. Abstract : In this study, we used the four‐state carrier model for brain GLUT1 to examine whether cellular glucose metabolism can be inferred from the accumulation of the fluorescent glucose analogue 6‐NBDG, which is increasingly employed for indirect determination of glucose transport and utilization in neurons and astrocytes. However, our findings show that the relation between 6‐NBDG uptake and glucose transport and utilization configures antiport not symport of the two substrates.